MMP9 Rs3918242 Polymorphism Affects Tachycardia-Induced MMP9 Expression in Cultured Atrial-Derived Myocytes but Is Not a Risk Factor for Atrial Fibrillation among the Taiwanese - Hsiao, Fu-Chih (Int J Mol Sci, 2016)
Matrix metalloproteinase (MMP) plays an important role in the pathogenesis of atrial fibrillation (AF). The MMP9 promoter has a functional polymorphism rs3918242 that can regulate the level of gene transcription. This study recruited 200 AF patients and 240 controls. The MMP9 rs3918242 was examined by polymerase chain reactions. HL-1 atrial myocytes were cultured and electrically stimulated. Right atrial appendages were obtained from six patients with AF and three controls with sinus rhythm undergoing open heart surgery. The MMP9 expression and activity were determined using immunohistochemical analysis and gelatin zymography, respectively. Rapid pacing induces MMP9 secretion from HL-1 myocytes in a time- and dose-dependent manner. The responsiveness of MMP9 transcriptional activity to tachypacing was significantly enhanced by rs3918242. The expression of MMP9 was increased in fibrillating atrial tissue than in sinus rhythm. However, the distribution of rs3918242 genotypes and allele frequencies did not significantly differ between the control and AF groups. HL-1 myocyte may secrete MMP9 in response to rapid pacing, and the secretion could be modulated by rs3918242. Although the MMP9 expression of human atrial myocyte is associated with AF, our study did not support the association of susceptibility to AF among Taiwanese subjects with the MMP9 rs3918242 polymorphism.